PEREKAYASAAN BRACHYTHERAPY MEDIUM DOSERATE - Atang Susila; Ari Satmoko; Ahmad Rifai; Kristiyanti Kristiyanti (BATAN, 2011)
DEVELOPMENT OF BRACHYTHERAPY MEDIUM DOSERATE . Brachytherapy has proven to be an effective treatment for different types of cancers and it become a common treatment modality in most radiotherapy clinics. PRPN has had experience in development of Low Dose Rate Brachytherapy for cervic cancer treatment. However the treatment process using LDR device needs 5 hours which makes the patient feel uncomfort. Therefore PRPN develops Medium Dose Rate Brachytherapy with radiation activity not more than 5 Currie. By using this system the expsure time will be shorter. The project is divided into two stages. Purchasing of TPS software and TDS design are held in 2010, and the construction will be in 2011. PEREKAYASAAN BRACHYTHERAPY MEDIUM DOSERATE. Brachytherapy telah menjadi suatu pengobatan yang efektif dari berbagai jenis kanker dan merupakan suatu modalitas pengobatan yang umum pada kebanyakan kilinik-klinik radiotherapi. PRPN telah memiliki pengalaman dalam pengembangan brachytherapy tipe Low Dose Rate (LDR)untuk terapi kanker servik (leher rahim). Namum proses penyinaran menggunakan tipe LDR dibutuhkan waktu lebih dari 5 jam sehingga kurang nyaman bagi pasien. Oleh karena itu PRPN mengembangkan brachytherapy tipe Medium Dose rate (MDR) dengan aktivitas sumber tidak lebih dari 5 Currie. Dengan sistem ini, diharapkan waktu penyinaran menjadi lebih pendek. Kegiatan ini dibagi menjadi dua tahun. Tahun 2010 terdiri dari pengadaan perangkat lunak TPS dan desain Treatment Delivery System (TDS) dan konstruksi tahun 2011.